Genome-Wide SNP Identification of The Elaeis guineensis x Elaeis oleifera Population - Wening, Sri; Adriwan Siregar, Heri; Suprianto, Edy; Setyawan, Dani; Y Rahmadi, Hernawan; Diah Setiowati, Retno; Arif, Mohamad; Yenni, Yurna; Supena, Nanang; Sujadi, Sujadi; Razak Purba, Abdul (Jurnal Penelitian Kelapa Sawit, 2021)
Efforts in finding DNA markers for favorable characters of Elaeis oleifera introgressed into Elaeis guineensis genome requires polymorphic DNA markers. To generate high number of polymorphic DNA markers, a genome-wide SNP identification was done by resequencing 12 individual samples using next generation sequencing (NGS) from an E. guineensis x E. oleifera (OxG hybrid) population comprising wild E. oleifera species, interspesific F1 hybrids, pseudo-backcrosses, and advanced E. guineensis samples. The reads generated from the 12 samples have good qualities and 96% of total filtered reads could be demultiplexed and assigned to the corresponding samples. After filtering and trimming, 84% of reads were retained for genome mapping and produced 5.7X to 10.42X genome coverage. Among the 34,410,224 identified SNPs, 98.7% of them were non-coding variants, and based on their location 69.1% of the total SNPs were intergenic SNPs. There were 5,618 SNPs out of the total generated SNPs that were validated using targeted genotyping by sequencing on 500 individuals, and 74% of the SNPs produced high quality calls in at least 95% of the samples. Principal component analysis using the SNPs correctly identified each sample’s genetic background. Thus, the SNPs had high quality and could be used to develop marker-assisted selection of the E. guineensis x E. oleifera breeding population.